2015
DOI: 10.1097/scs.0000000000002078
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Arthrocentesis Plus Hyaluronic Acid Injection in Patients With Wilkes Stage II and III Temporomandibular Joint Internal Derangement

Abstract: Arthrocentesis was reliable for treating both Wilkes II and III TMJ ID, and the treatment results were better in Wilkes III patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…Arthrocentesis is widely used in the TMJ for patients with a diagnosis of disc derangement. Only a few long-term studies have evaluated arthrocentesis and sodium hyaluronate in patients with different degenerative conditions in the TMJ (10,17,18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arthrocentesis is widely used in the TMJ for patients with a diagnosis of disc derangement. Only a few long-term studies have evaluated arthrocentesis and sodium hyaluronate in patients with different degenerative conditions in the TMJ (10,17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Injected HA was significantly more effective than injected corticosteroids in decreasing pain intensity in OA of the TMJ (4). Similarly, Ungor et al (10) concluded that HA injection in combination with arthrocentesis had promising effects on pain and TMJ function.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…is also possible. It was reported that arthrocentesis was reliable for treating Wilkes II and III stages of ID, and the treatment results were better in patients with advanced stage [28].…”
Section: Arthrocentesismentioning
confidence: 99%
“…Correspondingly, among the 60 cases of mandibular retraction, ADDWoR was observed in 56 patients. And therefore, disc displacement without reduction, especially combined with significant clinical symptoms such as pain, dysfunction, and maxillofacial abnormalities or failed to conservative therapies is general indication for invasive intervention treatment 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%